1963
DOI: 10.1542/peds.31.3.374
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Adrenaline and Noradrenaline in the Neonatal Period, and Infants With Respiratory Distress Syndrome and Placental Insufficiency

Abstract: The fluorometric method of Weil-Malherbe and Bone was used to investigate plasma catecholamine levels in the neonatal period. Full-term normal infants were found to have plasma adrenaline levels of 0.35 ± 0.64 µg/l and noradrenaline levels of 2.39 ± 2.69 µg/l. Premature infants had plasma adrenaline levels of 0.86 ± 1.21 µg/l and noradrenaline levels of 3.24 ± 2.03 µg/l. Twelve premature infants with the respiratory distress syndrome showed a significant and fourfold increase in adrenaline concentration and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1964
1964
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the plasma of preterm newborns, the concentrations of both adrenaline and noradrenaline are approximately two-fold higher compared with full-term babies [ 90 ]. Adrenaline levels have been found to be four-fold higher in preterm new-borns with respiratory distress syndrome, and eight-fold higher in those with placental insufficiency [ 90 ]. A study investigating fetal plasma noradrenaline responses to invasive procedures showed no correlation between maternal and fetal plasma levels of noradrenaline [ 91 ]; furthermore, although physiological infusion of adrenaline in pregnant sheep elevated fetal plasma adrenaline, the reduction of uterine, but not umbilical blood flow [ 92 ], suggests the likely barrier function of the placenta.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the plasma of preterm newborns, the concentrations of both adrenaline and noradrenaline are approximately two-fold higher compared with full-term babies [ 90 ]. Adrenaline levels have been found to be four-fold higher in preterm new-borns with respiratory distress syndrome, and eight-fold higher in those with placental insufficiency [ 90 ]. A study investigating fetal plasma noradrenaline responses to invasive procedures showed no correlation between maternal and fetal plasma levels of noradrenaline [ 91 ]; furthermore, although physiological infusion of adrenaline in pregnant sheep elevated fetal plasma adrenaline, the reduction of uterine, but not umbilical blood flow [ 92 ], suggests the likely barrier function of the placenta.…”
Section: Methodsmentioning
confidence: 99%
“…Some evidence has suggested that in hypertensive pregnancies, these transporters are downregulated, thus increased levels of endogenous catecholamines may compromise this placental defence [89]. In the plasma of preterm newborns, the concentrations of both adrenaline and noradrenaline are approximately twofold higher compared with full-term babies [90]. Adrenaline levels have been found to be four-fold higher in preterm new-borns with respiratory distress syndrome, and eightfold higher in those with placental insufficiency [90].…”
Section: Aim 2 Adrenergic Effects In Blood Vessel: Component Parts Of...mentioning
confidence: 99%